Buddhist Teachers’ Responses to Sexual Violence: Epistemological Violence in American Buddhism - Buckner, Ray (Journal of global buddhism, 2020)
In 2018, popular North American Buddhist teacher, Noah Levine, was accused of sexual assault and misconduct. Several Buddhist teachers responded in Levine’s defense through a seemingly neutral posture of “waiting to find out” the truth. This paper examines these teachers’ responses, asking the question: “Which Buddhist concepts are mobilized in responding to alleged sexual violence?” I find that these teachers respond to allegations with the language of not-knowing, equanimity, and right speech. They ask their communities to “wait and see” whether these allegations are true, with the unspoken assumption that they are not. I assert these responses use Buddhist teachings to uphold cis-masculine innocence by using hegemonic logics and commitments to downplay and delegitimize the phenomenon of sexual violence. I argue that these responses uphold hegemonic control within Buddhist communities, and conclude that a feminist response to allegations of misconduct requires centering survivors of sexual assault.